2016
DOI: 10.1002/jcop.21761
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Future Expectations on the Relationship Between Neighborhood Context and Adolescent Bullying Perpetration

Abstract: Bullying is an important public health issue among adolescents. Few studies have examined how neighborhood context affects adolescent bullying. The purpose of this study was to examine the relationship between neighborhood collective efficacy and bullying perpetration and sought to determine whether future expectations mediated this relationship. A sample of 196 7th-grade students (60% female; 27% White) from a Midwestern school completed measures assessing past 30-day bullying perpetration, neighborhood colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…However, leventhal and Brooks-Gunn (2000) have previously demonstrated that neighbourhood effects are usually mediated by more proximal factors such as individual-level psychological processes. We may conclude that strong social relationships increase adolescents' perceptions of a positive future (Schmidt, Pierce, & Stoddard, 2016) In turn, without contextual support youth may become disengaged from their future selves. Seginer and lilach (2004) found that a sense of loneliness among youth was associated with lower scores on motivation orientation, measured by value, expectance, and internal control of one's future plans.…”
Section: Individual and Ecological Influences During Adolescencementioning
confidence: 91%
“…However, leventhal and Brooks-Gunn (2000) have previously demonstrated that neighbourhood effects are usually mediated by more proximal factors such as individual-level psychological processes. We may conclude that strong social relationships increase adolescents' perceptions of a positive future (Schmidt, Pierce, & Stoddard, 2016) In turn, without contextual support youth may become disengaged from their future selves. Seginer and lilach (2004) found that a sense of loneliness among youth was associated with lower scores on motivation orientation, measured by value, expectance, and internal control of one's future plans.…”
Section: Individual and Ecological Influences During Adolescencementioning
confidence: 91%
“…In addition, affective relationships are established with peers and adults like teachers, who acquire special significance in this developmental stage [ 14 , 15 ]. School, as a socializing setting, forms part of a neighborhood or geographical zone which, in turn, influences the experiences and everyday relationships at school [ 16 , 11 ]. Therefore, the study of the structural violence present in zones or neighborhoods where schools are located has become a growing interest over the last years, as it may help explaining bullying phenomena [ 17 , 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the impact of this variable was greater than the presence of parental conflict which is a closer variable to child development. This suggests that interaction in extra-family social contexts, especially the community, has an important influence on the formation and expression of moral values, social norms and behavioral patterns (Lenzi et al, 2012;Schmidt, Pierce, & Stoddard, 2016;Vieno, Santinello, Pastore, & Perkins, 2007).…”
Section: Discussionmentioning
confidence: 99%